Variability between observers does not hamper detecting change over time in a temperate reef. (May 2022) - Azzola, Annalisa; Atzori, Fabrizio; Bianchi, Carlo Nike; Cadoni, Nicoletta; Frau, Francesca; Mora, Federico; Morri, Carla; Oprandi, Alice; Orrù, Paolo Emanuele; Montefalcone, Monica
Abstract: Marine ecosystems are subject to global and local impacts, both contributing to dramatic changes in coastal communities. Assessing such changes requires time series or the revisitation of sites first surveyed in the past. In both cases, data are not necessarily collected by the same observers, which could lead to a bias in the results. In the Marine Protected Area (MPA) of Capo Carbonara (Sardinia, Italy), established in 1998, rocky reef communities were first assessed in 2000 by two diving scientists. Twenty years later, the same rocky reefs were resurveyed using the same method by two other diving scientists. In both surveys, semi-quantitative data on conspicuous species were collected at five sites in four depth zones, providing the possibility of assessing change over time. To explore the influence of climate and local pressures, existing data on sea surface temperature, resident population, tourism and diving activities were analysed. The reef communities of the Capo Carbonara MPA have distinctly changed over time, mostly under the effect of seawater warming, as highlighted by the occurrence of thermophilic species and by other climate-related indicators. On the other side, species vulnerable to local human pressures have increased over time, demonstrating the effectiveness of the protection measures undertaken by the MPA. Comparing data collected by four different observers in the two periods demonstrated that change over time was significantly greater than variability between the observers. Highlights: Revisiting sites monitored in the past allows analysis of change over time. Data are rarely collected by the same researcher, this may influence sampling quality. Design of monitoring activities should consider the variability between observers. A drastic change in reef communities of the Capo Carbonara MPA was observed. Variability between observers did not hamper detecting change over time.